FR4 Antenna Design For Tropical Hailstorm Detection In Relation To Lightning Occurrence - Periannan, Dinesh (2019)
Lightning flash is an electrical discharge in air (dielectric breakdown) which emits electromagnetic (EM) fields across very wide spectra from a few Hertz up to visible wavelength. Lightning remote sensing has been used widely to measure the EM fields in various frequencies bands. Circular metal plate capacitive antenna made of iron or aluminum have been used widely for the front-end design of the remote sensing system. The circular metal plates are arranged in parallel and separated by insulators made of Teflon. However, three common problems encountered with the existing setting. First, both metals rust easily and could affect the reading of the EM fields. Second, the insulation Teflon separating the metal plates could become weak conductor and thus distort the EM fields reading. Third, the use of Teflon in between the parallel plates changes the overall permittivity value. The second problem is when most of the hailstorm were recorded at higher altitude. Through studies on meteorology context of NBEs in Florida and Great Plains showed strong correlation between lightning rates and ordinary lightning flash rates. Stronger storms have been observed to produce higher percentage NBEs while weaker storms produce less or no NBEs. In this thesis, in order to overcome these problems, we propose a cheaper and lighter alternative to iron and aluminum plates by changing to FR4 copper plate. Rectangular FR4 copper plate capacitive antenna A3 have been designed and constructed. The rectangular A3 FR4 copper plate has been found to have comparable impedance and capacitance values to the iron-based circular metal plate. Analysis of the wave shape and peak amplitude ratio showed comparable performance between both antennas. Secondly, there is no studies has been done in tropical region, so this thesis is motivated to provide the first studies of Tropical hailstorm in mid latitude. After replacing the antenna for lightning measurement system, data were collected using buffer circuit (fast field and slow field system) connected with picoscope (PC based oscilloscope) and presented the evolution (5-minute flash rate) of two tropical hailstorms that occurred in Malaysia at two sites namely Bukit Jalil (approximately 112 km from exact location) and Sungai Udang (approximately 22 km from exact location) with the objective to understand the relationship of the hailstorms with Negative Narrow Bipolar Event (–NBE) and Positive Cloud-to-Ground (+CG) flashes. For Bukit Jalil hailstorm, within 5 minutes period between 10:30 and 10:35, 16 –NBEs have been detected where else for Sungai Udang hailstorm, starting 18:55 until 19:35, 60 +CGs flashes were detected when the hails were reported to hit the ground in duration of 40 minutes. First conclusion for the antenna, rectangular A3 FR4 copper plate antenna can be used as replacement for the existing iron- or aluminium-based circular metal plates antenna. Second conclusion for the hailstorm, based on the results of these 2 tropical hailstorms, clearly stronger convection does not relate only to higher –NBEs flash rate but also highly correlated to +CGs flash rate.